Buffer-dependent regulation of aquaporin-1 expression and function in human peritoneal mesothelial cells - Zhai, Yihui; Bloch, Jacek; Hömme, Meike; Schaefer, Julia; Hackert, Thilo; Philippin, Bärbel; Schwenger, Vedat; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2012)
BackgroundBiocompatible peritoneal dialysis fluids (PDF) are buffered with lactate and/or bicarbonate. We hypothesized that the reduced toxicity of the biocompatible solutions might unmask specific effects of the buffer type on mesothelial cell functions.MethodsHuman peritoneal mesothelial cells (HPMC) were incubated with bicarbonate (B-)PDF or lactate-buffered (L-)PDF followed by messenger RNA (mRNA) and protein analysis. Gene silencing was achieved using small interfering RNA (siRNA), functional studies using Transwell culture systems, and monolayer wound-healing assays.ResultsIncubation with B-PDF increased HPMC migration in the Transwell and monolayer wound-healing assay to 245 ± 99 and 137 ± 11% compared with L-PDF. Gene silencing showed this effect to be entirely dependent on the expression of aquaporin-1 (AQP-1) and independent of AQP-3. Exposure of HPMC to B-PDF increased AQP-1 mRNA and protein abundance to 209 ± 80 and 197 ± 60% of medium control; the effect was pH dependent. L-PDF reduced AQP-1 mRNA. Addition of bicarbonate to L-PDF increased AQP-1 abundance by threefold; mRNA half-life remained unchanged. Immunocytochemistry confirmed opposite changes of AQP-1 cell-membrane abundance with B-PDF and L-PDF.ConclusionsPeritoneal mesothelial AQP-1 abundance and migration capacity is regulated by pH and buffer agents used in PD solutions. In vivo studies are required to delineate the impact with respect to long-term peritoneal membrane integrity and function.
Gesehen am 27.07.2018